Imena sobstvennye i zaglaviâ v proze i poèzii Borisa Pasternaka - Fateeva, Nataliâ A. (Stylistyka, 1994)
The article is devoted to the investigation of semantic functions of proper names and titles in Pasternak’s prose and poetry. Both of them possess special power in modelling of author’s world. Titles acquire the power due to their metatextual position over and above а text and а whole cycle of texts or а book of verses. Proper names generate multidemensional relations in the frame of а certain text as well as in the frame of the whole poetical idiostyle. That’s why proper names often appear in titles and in such way fix their text generating function and significance (compare "Detstvo Ljuvers", "Spectorsky", "Doctor Zivago", etc.). Thus, proper names and titles prove to Ье the markers of inner structure of the poet’s world. According to these markers we try to reveal the main concepts and principles of organization of Pasternak’s world. Тhе main world generating principle of Pasternak turns out to Ье ’reflection’and it is closely connected with idea of ’eye-sight’. The embodiment of this principle can Ье found in such titles as "Miпor" and titles-proper names Reliquimini, Spectorsky. The main principle of Pasternak’s world development is synthesis of natural and spiritual growth. The sourses of this synthesis lie in his own surname Pasternak (lit.’grass, parsnip’). Тhat’s why the leading concepts of Pastemak’s world are: ’life’ , ’recreation’ as opposed to ’death’ (embodied in titles "Sestra moja-zizn" ("Му sister- life") and "Doctor Zivago"); the four natural elements (earth, air (wind), water and fire); ’etemal feminity’ as а basis of the world (incamated in the image of а "Girl" in "Му sister -life" and "Detstvo Ljuvers" and than in "Мagdalina" and "Eva"). The main attention in the article is paid on the titles of the books of verses which show the evolution of Pastemak’s idea of the universe and changes in his creative manner. The analysis of the proЫem of entitling/non-entitling of 1yrical poems in the frame of the book of verses shows high percent of inner non-entitling in two books: "Nacal’naja pora" ("Initial time") and "Vtoroe rozdenie" (, Second birth"). Тhis phenomenon can Ье considered as marking of two initia1 states of the poet’s system. Тhе final state of the system is marked Ьу the title of the 1ast book of verses , Кogda razguljaetsja" ("When it has cleared up") and its 1ast роет "Edinstvennye dni" ("The only days"): it is the way to the Etemity according to the principle of sun circulation. Pastemak finishes his way on the spring equinox when the sun wins the victory over the darkness.